Análise econômica da interação entre a infraestrutura da saúde pública e privada no Brasil - Nishijima, Marislei; Cyrillo, Denise Cavallini; Biasoto Junior, Geraldo [UNESP] (Instituto de Economia da Universidade Estadual de Campinas, 2010)
This article analyses how the last Brazilian Constitution - which regulates the universal rights of public health care - has negatively impacted the distribution of health care in terms of the access that Brazilians with lower incomes have to public health care. The specific way that the public and private sectors of health care functions has caused this to happen. This phenomenon was indirectly tested using supplementary health economics survey data, together with a traditional household survey, the Pesquisa Nacional de Amostra por Domicílio (PNAD), from 1998. Logit and probit models were used to analyze the data, and the results supported the proposed hypothesis.

Este artigo analisa de que forma a interação entre o setor público e privado de saúde da economia brasileira, avaliando como a sua estrutura produtiva, aliada ao aparato legal referente ao período anterior à regulação da Agência Nacional de Saúde Suplementar, pode ter causado um impacto negativo sobre o acesso dos brasileiros de baixa renda aos bens públicos de saúde. Para dar suporte aos argumentos apresentados, foram utilizados os microdados do suplemento saúde da PNAD de 1998, analisados por meio de modelos logit e probit tendo em vista o caráter qualitativo da variável dependente. Os resultados sugerem evidências favoráveis à hipótese proposta.
Economic analysis of the Brazilian public and private health infrastructure
Keywords: Medical care; Public health; Private health; Health insurance; ANS; Assistência médica; Saúde pública; Saúde privada; Seguro de saúde; ANS